Meta-Analysis the Effect of Oral Combination Contraceptive on Hypertension and Stroke - Zuhaira, Ulul Azmi; Pamungkasari, Eti Poncorini; Widyaningsih, Vitri (Journal of Maternal and Child Health, 2022)
Background: Combined oral contraceptives are a form of contraception that are considered safe and effective for some women, but this does not rule out the possibility that combined oral contraceptives contribute to adverse health effects. Several epidemiological studies have shown that oral contraceptives have adverse effects on women's health. The use of contraceptive pills containing the hormones estrogen and progesterone can cause an increase in blood pressure and also stroke if used continuously. The purpose of this study was to estimate the magnitude of the risk of using combined oral contraceptives on the incidence of hypertension and stroke with a meta-analysis study. Subjects and Method: This was a systematic review and meta-analysis using PRISMA flowchart diagram guidelines. The article search process was carried out between 2007-2022 using 3 databases, including Google Scholar, PubMed, and Science Direct. The keywords used in the database search were “oral contraceptive” OR “contraceptive pills” OR “combined oral contraceptive” AND “hypertension” OR “blood pressure” AND “stroke” AND “women of reproductive age”. The inclusion criteria for full text articles using case control observational methods, articles using English, and articles using multivariate analysis with adjusted Odds Ratio results. Articles that have met the requirements are analyzed using the RevMan 5.3 application. Results: A total of 14 articles with case-control study designs originating from China, Ethiopia, the United States, Italy, and the Netherlands were carried out in a meta-analysis in this study. Meta-analysis of 7 articles showed that the effect of using combined oral contraceptives was to increase the incidence of hypertension 1.44 times compared to those who did not use combined oral contraceptives (aOR= 1.44; 95% CI= 1.12 to 1.84; p= 0.004). Meanwhile, 7 articles showed that the effect of using combined oral contraceptives was to increase the incidence of stroke by 2.08 times compared to those who did not use combined oral contraceptives (aOR= 2.08; 95% CI= 1.48 to 2.92; p < 0.001). Conclusion: Combined oral contraceptives increase the risk of hypertension and stroke. Keywords: combined oral contraceptives, hypertension, stroke, meta-analysis Correspondence:Ulul Azmi Zuhaira. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: ululazmizuhaira@gmail.com. Mobile: +6282245012258.